THE SPILLOVER EFFECTS OF FDI ON LABOR PRODUCTIVITY OF FIRMS: EVIDENCE FROM THE FIVE PRIORITY MANUFACTURING INDUSTRIES IN INDONESIA - Juda, Martin; Kudo, Toshihiro (Jurnal Ekonomi dan Pembangunan, 2020)
This study aims to investigate the effects of FDI spillover on labor productivity of the firms in the five priority manufacturing sector industries in Indonesia, namely food and beverages, textiles, wearing apparel and footwear, chemicals and pharmaceuticals, electronics, and automotive and transport equipment industries. Using unbalanced firm-level data from 2000 to 2015, we find positive spillover effects in the horizontal linkages, which measure the presence of foreign firms on the labor productivity of local firms in the same industry. However, the effects of FDI on the labor productivity of domestic in backward linkages shows negative results, which means foreign buyers fail to give benefits to domestic suppliers. Moreover, the relationship between foreign suppliers and domestic buyers in the forward linkages also show negative spillover effects. These findings are also in line when the analyses are disaggregated into each industry, except for the electronics industry. Based on the different results of the three linkages of spillover effects, our findings suggest that the FDI spillover has not provided comprehensive benefits for local firms.